Inhibition performance of uniconazole on steel corrosion in simulated concrete pore solution: An eco-friendly way for steel protection - Yuanyuan Meng; Shuangxi Li; Zhi Zhang (Heliyon, 2024)
Corrosion inhibitors play a vital role in impeding the corrosion process of steel bars within concrete structures exposed to corrosive environments. Nevertheless, conventional corrosion inhibitors pose environmental risks. In contrast, contemporary studies have explored corrosion inhibitors that are eco-friendly. However, these inhibitors are burdened by high costs and complex production processes, impeding the widespread application in concrete structures. Consequently, this study presents an innovative solution by incorporating uniconazole, an agricultural fungicide, as a corrosion inhibitor for steel bars in concrete structures. The steel bars were exposed to corrosion within a simulated concrete pore solution containing 0.6 mol/L NaCl, both with and without the presence of uniconazole. The morphology and hydrophilicity of the steel bar surface were investigated via optical microscope and contact angle experiments. Electrochemical tests (open circuit potential, potentiodynamic polarization, electrochemical impedance spectroscopy, and Mott-Schottky analysis) and X-ray photoelectron spectroscopy were employed to investigate the corrosion inhibition performance and mechanism of uniconazole. The results demonstrate that uniconazole elevates the hydrophobicity and contributes to the corrosion inhibition of steel bars. Electrochemical test results indicate that as the concentration of uniconazole increases from 1 × 10−4 mol/L to 1 × 10−3 mol/L, the inhibition efficiency likewise demonstrates a corresponding increase, escalating from around 50 %–90 %. Uniconazole molecules function as mixed-type inhibitors, exhibiting characteristics of both anode-type and cathode-type inhibitors. The adsorption of uniconazole enhances the stability and thickness of the passive-adsorbed layer on the steel surface, effectively impeding the charge transfer process and obstructing the interaction of corrosive substances with the base metal. In summary, the application of uniconazole exhibits the highlights of efficient, cost-effective, environmentally friendly, and the potential for scalable production. This positions uniconazole as a promising candidate for use as a corrosion inhibitor in the domain of concrete structures.